Optimization of Audio System Wireles Transmitter Using Green Laser: Nurrisma Puspitasari, Adnan Wahyu Dwiputra, Sudarsono Sudarsono, Gatut Yudoyono, Gontjang Prajitno, Bachtera Indarto - Nurrisma Puspitasari Nurrisma Puspitasari; Adnan Wahyu Dwiputra Adnan Wahyu Dwiputra; Sudarsono Sudarsono; Gatut Yudoyono Gatut Yudoyono; Gontjang Prajitno Gontjang Prajitno; Bachtera Indarto Bachtera Indarto (Jurnal Fisika dan Aplikasinya, 2024)
Nowadays, many activities are done digitally using wireless technology. Wireless technology is the mainstay of communication, but along with the development of the times, there is a wireless technology that utilizes LASER. There has been quite a lot of research on audio systems with wireless transmitters, but none have analyzed the potential of green lasers to obtain the optimal wavelength for communication. This study aims to design a voice transmission system using a laser, determine the relationship between input voltage and laser light intensity, and compare the output frequency with the input frequency. There are three types of measurements: light intensity and distance, laser diode voltage and intensity, and output frequency compared to input frequency. The audio input signal from the source is modulated and transmitted through a laser light medium. The laser beam is then fired into a receiver circuit that can demodulate the signal which is then sent to the output device in the form of a speaker. The study found that the output frequency had the highest error percentage of 38.70% at 125 Hz and the lowest error percentage of 0.07% at 500 Hz when compared to the input frequency. The biggest mistake comes from the volume dropping at a low frequency. The oscilloscope reading is not accurate due to the smaller volume, which leads to a high deviation value and affects the system performance negatively.